CXCR4 blockade reduces the severity of murine heart allograft rejection by plasmacytoid dendritic cell-mediated immune regulation - Fu, Jian; Lehmann, Christian; Wang, Xinning; Wahlbuhl, Mandy; Allabauer, Ida; Wilde, Benjamin; Amon, Lukas; Dolff, Sebastian; Cesnjevar, Robert; Kribben, Andreas; Wölfle, Joachim; Rascher, Wolfgang; et al. (Scientific Reports, 2021)
Allograft-specific regulatory T cells (Treg cells) are crucial for long-term graft acceptance after transplantation. Although adoptive Treg cell transfer has been proposed, major challenges include graft-specificity and stability. Thus, there is an unmet need for the direct induction of graft-specific Treg cells. We hypothesized a synergism of the immunotolerogenic effects of rapamycin (mTOR inhibition) and plerixafor (CXCR4 antagonist) for Treg cell induction. Thus, we performed fully-mismatched heart transplantations and found combination treatment to result in prolonged allograft survival. Moreover, fibrosis and myocyte lesions were reduced. Although less CD3+ T cell infiltrated, higher Treg cell numbers were observed. Noteworthy, this was accompanied by a plerixafor-dependent plasmacytoid dendritic cells-(pDCs)-mobilization. Furthermore, in vivo pDC-depletion abrogated the plerixafor-mediated Treg cell number increase and reduced allograft survival. Our pharmacological approach allowed to increase Treg cell numbers due to pDC-mediated immune regulation. Therefore pDCs can be an attractive immunotherapeutic target in addition to plerixafor treatment.
CRIS-Team Scopus Importer:2021-12-24